An Integrated Method Using Fuzzy AHP and TOPSIS Method for Supplier Selection in Recycled Lubricating Oil Industry for GSCM - Dr. Karuna Kumar G., Dr. B. Karuna Kumar, Seelam Krugon, S. Venkata Reddy (International Journal of Advanced Science and Technology, 2020)
Recycling is one of the best tools to reduce hazard waste. According to the law of government and company policies have their responsibilities to collect their end life products and safety disposal or recycle of end life products. As a result, so many industries arrange the agencies to collect their end products and sent to the recycling industries, after recycling again they collect their recycling products and sold to secondary markets or they use in their companies. In this case study the agencies or the managers select an ideal recycler (suppliers) to send their end products and collect the recycled products for resale or reuse.          A coordinate strategy proposed with fluffy AHP and TOPSIS technique with models of Price, Relative Density, Purity and Boiling Range for assessed five providers this approach pertinent for to choose a perfect supplier. A contextual investigation directed Recycled Lubricating Oil industry and results are very fulfill.